Circling the wagons or opening the circle. Issue 4 (28th September 2020) - Pally, Marcia
Abstract: "To approach eudaimonia or human flourishing, " Darcia Narvaez writes, "one must have a concept of human nature… a normal baseline." This article asks: what is the human baseline so that we may develop public policy to suit and advance human and planetary flourishing? It proposes that our "baseline" is relational, where each person becomes her singular self through networks of relations with others and planet. Relationality is explored through Trinity, covenant, evolutionary biology, and psychology. The article concludes that public policy must be grounded not in "us‐them" thinking but in relationality as this is how we are created.